Analysis of the Motor Control System for Moving Goods Using Google Assistant - Dimas Setiawan (Natural Sciences Engineering and Technology Journal, 2021)
Developments in robotics science have positive impact in the industrial sector. One example is the process of moving an item/object from one place to another. This study aimed to test the motion system, namely a DC motor that functions as a motor for carrying goods. The method used is input from commands given by the user via a smartphone with voice access. As an intermediary, a bluetooth connection is used so that commands can be sent from a smartphone to the control circuit. The controller used is the AVR type, namely atmega 328 on the Arduino Uno board. At the output, there are relays and current amplifiers that function as motor drivers. The user will give orders via a smartphone where on the smartphone runs an application, namely a voice to text converter. The application will convert the human voice into text and send via bluetooth to the controller. The Arduino controller will identify the command code and execute it, namely controlling the robot's motion in the direction desired by the user, for example forward, backward left and right or towards a predetermined point. In conclusion, the analysis of the drive motor control system was successfully carried out by calculating and measuring the power of the DC motor. The control system program was successfully created in C language using arduino. The program successfully runs and controls the motor motion properly according to the user's command via the Google assistant.